Numerical Determination of the Frictional Coefficients of a Fluid Film Journal Bearing Considering the Elastohydrodynamic Lubrication and the Asperity Contact Force - Gwanghee Hong; Kyobong Kim; Youngjun Park; Gunhee Jang (Machines, 2022)
This paper proposes a numerical method to investigate the frictional characteristics of a fluid film journal bearing considering the elastohydrodynamic lubrication and the asperity contact force. We solved the average Reynolds equation by utilizing the FEM to determine the hydrodynamic force developed by the lubricant of the journal bearing. We also used a modified GT model (Greenwood–Tripp model) developed by Greenwood and Tripp to decompose the asperity contact force into normal and tangential directions. Once we applied those forces to a rotor, we solved the equations of motion of a flexible shaft to determine the friction coefficient. We verified the proposed method by comparing the calculated friction coefficient with the measured one of journal bearings conducted by prior researchers. Then, the proposed method was applied to investigate the frictional characteristics of a journal bearing of a scroll compressor on which dynamic loads are applied. This paper can contribute to developing robust rotor systems supported by journal bearings.